Cometabolic degradation of lincomycin in a Sequencing Batch Biofilm Reactor (SBBR) and its microbial community. (August 2016) - Li, Yancheng; Zhou, Jian; Gong, Benzhou; Wang, Yingmu; He, Qiang
Highlights: The lincomycin was degraded effectively in cometabolic system with glucose as growth substrate. Roseovarius, Thiothrix, Halomonas, Ignavibacterium, and TM7_genus_incertae_sedis were dominant populations. Functional groups of lincomycin were effectively degraded. Cometabolism may be synergistically caused by different functional dominant bacteria. Abstract: Cometabolism technology was employed to degrade lincomycin wastewater in Sequencing Batch Biofilm Reactor (SBBR). In contrast with the control group, the average removal rate of lincomycin increased by 56.0% and Total Organic Carbon (TOC) increased by 52.5% in the cometabolic system with glucose as growth substrate. Under the same condition, Oxidation–Reduction Potential (ORP) was 85.1 ± 7.3 mV in cometabolic system and 198.2 ± 8.4 mV in the control group, indicating that glucose changed the bulk ORP and created an appropriate growing environment for function bacteria. Functional groups of lincomycin were effectively degraded in cometabolic system proved by FTIR and GC–MS. Meanwhile, results of DGGE and 16S rDNA showed great difference in dominant populations between cometabolic system and the control group. In cometabolic system, Roseovarius (3.35%), Thiothrix (2.74%), Halomonas (2.49%), Ignavibacterium (2.02%), and TM7_genus_incertae_sedis (1.93%) were verified as dominant populations at genus level. Cometabolism may be synergistically caused by different functional dominant bacteria.